Fiqh Talak Sebagai Objek Kekerasan - Muttaqin, Muhammad Riki Zaenal; Anwar, Syahrul (Sharia Journal and Education Center Publishing, 2025)
This paper examines how the practice of ṭalāq can be misused as an instrument of abuse whether physical, psychological, or structural and maps the normative safeguards within Islamic jurisprudence (fiqh) and Indonesian positive law to prevent such misuse. The foundations of fiqh emphasize the principle of lā ḍarar wa lā ḍirār (no harm and no reciprocating harm), the principle of mu‘āsyarah bi al-ma‘rūf (living together in a good and respectful manner), and the ethical-procedural boundaries of divorce as outlined in the Qur’an. Meanwhile, the Compilation of Islamic Law (KHI) requires ṭalāq to be declared before a Religious Court, and the Domestic Violence Law (UU PKDRT) imposes sanctions if divorce is accompanied by violence. Thus, ṭalāq must not be employed as a means of intimidation, coercion, or perpetuating harmful relationships.